PEMAKNAAN ALIRAN DUALISTIS PERSPEKSTIF HUKUM PIDANA DALAM KUHP NASIONAL - Anwar, Reski (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2023)
The presence of criminal framework in WvSNI relies on legality rules which state that an act is considered criminal if the actions and errors are fulfilled in an article formulation, thus causing the discipline in WvSNI to be felt to be very inflexible in terms of its enforcement. Meanwhile, the legality paradigm has moved to a dualistic principle or teaching that separates criminal acts and criminal responsibility. The National Criminal Code has firmly implemented this dualistic teaching as one component of the criminal framework, so that the link between legal legal certainty and justice can be recognized in a balanced manner in court decisions. The presence of the principle of legality in dualistic teachings in the framework of criminal regulations in Indonesia, especially in WvSNI, has a very big situation in the framework of law enforcement, where the ideas of unlawfulness and error are components of criminal acts or also called monistic teachings. WvsNI does not understand the connection between criminal risk and the perpetrator, but criminal responsibility is only referred to solely based on forgiving and justifying reasons. Therefore, many problems occur within the framework of law enforcement, where enforcement officials focus on legal certainty rather than legal justice itself. Meanwhile, in the doctrine known in criminal law there is the principle of 'There is no crime without guilt' or also called dualistic teaching. In short, this teaching separates criminal acts and criminal responsibility. Criminal acts discuss the issue of 'acts', while the issue of whether the 'individual' who committed the act can be considered responsible is an alternative issue. In the current situation, dualistic teachings play a very large role in overcoming the rigid nature of problems within the framework of law enforcement, especially for those implementing regulations. So when there is a conflict between legal beliefs and justice, what must be the focus is justice. Kerangka pemidanaan dalam WvSNI bergantung pada aturan legalitas yang menghadapkan bahwa suatu perbuatan dianggap pidana jika perbuatan dan kesalahannya terpenuhi dalam sebuah rumusan pasal, sehingga menyebabkan disiplin dalam WvSNI dirasakan sangat tidak fleksibel dalam penyelesaian penegakannya. Sedangkan paradigma legalitas telah berpindah ke asas atau ajaran dualistik yang memisahkan tindak pidana dan pertanggungjawaban pidana. KUHP Nasional secara tegas telah menjalankan ajaran dualistik tersebut sebagai salah satu komponen kerangka pidana, sehingga keterkaitan antara kepastian hukum yang sah dan keadilan dapat diakui secara seimbang pada putusan pengadilan. Hadirnya asas legalitas dalam ajaran dualistis dalam kerangka peraturan pidana di Indonesia, khususnya dalam WvSNI, mempunyai situasi yang sangat besar dalam kerangka penegakan hukum, dimana gagasan sifat melawan hukum dan kesalahan merupakan komponen dari perbuatan pidana atau disebut juga ajaran monistik. WvsNI tidak memahami keterkaitan antara risiko pidana dan sipelaku, namun pertanggungjawaban pidana hanya dirujuk semata-mata berdasarkan alasan pemaaf dan pembenar. Oleh karena itu, banyak permasalahan terjadi dalam kerangka penegakan hukum, di mana aparatur penegak berfokus pada kepastian akan hukum daripada keadilan hukum itu sendiri. Sementara itu, dalam doktrin yang dikenal dalam hukum pidan ada asas ‘Tiada pidana tanpa kesalahan’ atau disebut juga ajaran dualistis. Singkatnya dalam ajaran ini memisahkan antara tindak pidana dan pertangunggjawaban pidana. Tindak pidana membahas menyangkut persoalan 'perbuatan', sedangkan persoalan apakah 'individu' yang melakukan perbuatan dapat dianggap bertanggung jawab merupakan persoalan alternatif. Dalam situasi saat ini, ajaran dualistik memainkan peranan yang sangat besar dalam mengatasi sifat kaku permasalahan dalam kerangka penegakan hukum, khususnya bagi para pelaksana peraturan. Jadi ketika ada konflik antara keyakinan hukum dan keadilan, maka yang harus menjadi fokus adalah keadilan. Kata Kunci: Aliran Dualistis, Tindak Pidana, Pertanggungjawaban Pidana, Hukum Pidana, KUHP Nasional.